Phenolic acids from medicinal and edible homologous plants: a potential anti-inflammatory agent for inflammatory diseases - Xie, Jingchen; Xiong, Suhui; Li, Yamei; Xia, Bohou; Li, Minjie; Zhang, Zhimin; Shi, Zhe; Peng, Qiuxian; Li, Chun; Lin, Limei; Liao, Duanfang (Frontiers in Immunology, 2024)
Inflammation has been shown to trigger a wide range of chronic diseases, particularly inflammatory diseases. As a result, the focus of research has been on anti-inflammatory drugs and foods. In recent years, the field of medicinal and edible homology (MEH) has developed rapidly in both medical and food sciences, with 95% of MEH being associated with plants. Phenolic acids are a crucial group of natural bioactive substances found in medicinal and edible homologous plants (MEHPs). Their anti-inflammatory activity is significant as they play a vital role in treating several inflammatory diseases. These compounds possess enormous potential for developing anti-inflammatory drugs and functional foods. However, their development is far from satisfactory due to their diverse structure and intricate anti-inflammatory mechanisms. In this review, we summarize the various types, structures, and distribution of MEHP phenolic acids that have been identified as of 2023. We also analyze their anti-inflammatory activity and molecular mechanisms in inflammatory diseases through NF-κB, MAPK, NLRP3, Nrf2, TLRs, and IL-17 pathways. Additionally, we investigate their impact on regulating the composition of the gut microbiota and immune responses. This analysis lays the groundwork for further exploration of the anti-inflammatory structure-activity relationship of MEHP phenolic acids, aiming to inspire structural optimization and deepen our understanding of their mechanism, and provides valuable insights for future research and development in this field.